2015
DOI: 10.2337/db14-1397
|View full text |Cite
|
Sign up to set email alerts
|

BAMBI Elimination Enhances Alternative TGF-β Signaling and Glomerular Dysfunction in Diabetic Mice

Abstract: BMP, activin, membrane-bound inhibitor (BAMBI) acts as a pseudo-receptor for the transforming growth factor (TGF)-β type I receptor family and a negative modulator of TGF-β kinase signaling, and BAMBI−/− mice show mild endothelial dysfunction. Because diabetic glomerular disease is associated with TGF-β overexpression and microvascular alterations, we examined the effect of diabetes on glomerular BAMBI mRNA levels. In isolated glomeruli from biopsies of patients with diabetic nephropathy and in glomeruli from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 54 publications
(105 reference statements)
3
48
0
Order By: Relevance
“…Reduced BAMBI expression potentiated TGF-β-induced responses. These results are in line with a previous study where TGF-β-induced α-SMA and collagen I expression was enhanced by down-regulation of BAMBI (40).…”
Section: Discussionsupporting
confidence: 93%
“…Reduced BAMBI expression potentiated TGF-β-induced responses. These results are in line with a previous study where TGF-β-induced α-SMA and collagen I expression was enhanced by down-regulation of BAMBI (40).…”
Section: Discussionsupporting
confidence: 93%
“…In vivo experiment showed that BAMBI transduction abolished protumor effects of an orthotopic breast cancer xenograft model (43) and modulated the effects of diabetes via inhibiting TGF-β signaling (44). Our study found that BAMBI overex pression and β-sitosterol suppressed tumor growth in NSCLC xenografts, revealing the antitumor effect of BAMBI overexpression and β-sitosterol.…”
Section: Discussionmentioning
confidence: 53%
“…Fig. 2) [24]. These mRNA (UMOD, SLC12A1, NDUFB2, OAZ1, PPARGC1A, NFE2L2, CD24, SMAD1) were selected for qPCR screening and validation in this larger study described here.…”
Section: Resultsmentioning
confidence: 99%